A microfluidic bone marrow chip for the safety profiling of biologics in pre-clinical drug development - Leopold Koenig; Laurent Juglair; Thi Phuong Tao; Susanne Fischer; Inga Clausen; Sabine Imhof-Jung; Niels Janssen; Robert Mader; Daniel Marbach; Jens Niewoehner; Annika Winter; Desirée Schubert (Communications Biology)
Abstract Hematologic adverse events are common dose-limiting toxicities in drug development. Classical animal models for preclinical safety assessment of immunotherapies are often limited due to insufficient cross-reactivity with non-human homologous proteins, immune system differences, and ethical considerations. Therefore, we evaluate a human bone marrow (BM) microphysiological system (MPS) for its ability to predict expected hematopoietic liabilities of immunotherapeutics. The BM-MPS consists of a closed microfluidic circuit containing a ceramic scaffold covered with human mesenchymal stromal cells and populated with human BM-derived CD34+ cells in chemically defined growth factor-enriched media. The model supports on-chip differentiation of erythroid, myeloid and NK cells from CD34+ cells over 31 days. The hematopoietic lineage balance and output is responsive to pro-inflammatory factors and cytokines. Treatment with a transferrin receptor-targeting IgG1 antibody results in inhibition of on-chip erythropoiesis. The immunocompetence of the chip is established by the addition of peripheral blood T cells in a fully autologous setup. Treatment with T cell bispecific antibodies induces T cell activation and target cell killing consistent with expected on-target off-tumor toxicities. In conclusion, this study provides a proof-of-concept that this BM-MPS is applicable for in vitro hematopoietic safety profiling of immunotherapeutics.